Causal relationship between body mass index and anal fistula: a two-sample Mendelian randomization study - Chen, Bo; Liu, Yicheng; Wang, Yueting; Wang, Qingming (Frontiers in Genetics, 2024)
Background Significant evidence has been documented regarding the intricate connection between the development of anal fistula (AF) and the composition of Body Mass Index(BMI). Nevertheless, due to the inherent limitations of reverse causality and confounders inherent in observational studies, this relationship remains unclarified. Our study aims to reveal the causal impact between BMI and AF, as well as identify its associated risk factors, thereby providing a more comprehensive understanding of this complex interaction. Methods Single nucleotide polymorphisms (SNPs) identified through Genome-Wide Association Studies (GWAS) databases were used as instrumental variables for analysis. BMI served as the exposure variable, with six pooled GWAS datasets included. AF was the outcome variable. The Inverse Variance Weighted (IVW) method was used as the primary analytical technique, with MR-Egger regression, Weighted Median (WME) estimation, and Multiplicity Residual Sum and Outlier (MR-PRESSO) tests serving as secondary validations of the IVW results. Odds ratios (OR) were utilized as indicators to evaluate the causal relationship between BMI and AF. Results A total of 738 SNPs strongly associated with the exposure were identified as instrumental variables. The IVW results demonstrated a positive correlation between BMI and the risk of AF. The MR-Egger analysis yielded P-values greater than 0.05, indicating no pleiotropic effects among the selected SNPs. Cochran's Q test also resulted in P-values greater than 0.05, suggesting no significant heterogeneity among the instrumental variables. The MR-PRESSO analysis revealed no horizontal pleiotropy or outliers potentially violating the causal assumption (P＞0.05).